ESM bibliografiniame darbe - Černiauskienė, Izabelė; Liberis, Stasys (Knygotyra, 1976)
The first experiment in usings computer „Minsk–22“ to compile an alphabetical index to the joint catalog of foreign mathematical periodicals of the biggest libraries of the Lithuanian SSR is described.The aim of the experiment was to study practically the technology of the preparation of bibliographic publications with the help of computers, the possibilities of using computers in the compilations of more complex and comprehensive publications, to evaluate the effectiveness of this method.